Proposed refined diagnostic criteria and classification of eosinophil disorders and related syndromes - Valent, Peter; Klion, Amy D.; Roufosse, Florence; Simon, Dagmar; Metzgeroth, Georgia; Leiferman, Kristin M.; Schwaab, Juliana; Butterfield, Joseph H.; Sperr, Wolfgang Reinhard; Sotlar, Karl; Vandenberghe, Peter; Hoermann, Gregor; et al. (Allergy, 2023)
Eosinophilia and eosinophil activation are recurrent features in various reactive states and certain hematologic malignancies. In patients with hypereosinophilia (HE), HE-induced organ damage is often encountered and may lead to the diagnosis of a hypereosinophilic syndrome (HES). A number of known mechanisms and etiologies contribute to the development of HE and HES. Based on these etiologies and the origin of eosinophils, HE and HES are divided into primary forms where eosinophils are clonal cells, reactive forms where an underlying reactive or neoplastic condition is detected and eosinophils are considered to be “non-clonal” cells, and idiopathic HE and HES in which neither a clonal nor a reactive underlying pathology is detected. Since 2012, this classification and the related criteria have been widely accepted and regarded as standard. However, during the past few years, new developments in the field and an increasing number of markers and targets have created a need to update these criteria and the classification of HE and HES. To address this challenge, a Working Conference on eosinophil disorders was organized in 2021. In this conference, a panel of experts representing the relevant fields, including allergy, dermatology, hematology, immunology, laboratory medicine, and pathology, met and discussed new markers and concepts as well as refinements in definitions, criteria and classifications of HE and HES. The outcomes of this conference are presented in this article and should assist in the diagnosis and management of patients with HE and HES in daily practice and in the preparation and conduct of clinical trials.
Erstmals veröffentlicht: 7. Oktober 2022
Gesehen am 30.07.2024